Neonatal Murine Model of Coxsackievirus A2 Infection for the Evaluation of Antiviral Therapeutics and Vaccination - Ji, Wangquan; Qin, Luwei; Tao, Ling; Zhu, Peiyu; Liang, Ruonan; Zhou, Guangyuan; Chen, Shuaiyin; Zhang, Weiguo; Yang, Haiyan; Duan, Guangcai; Jin, Yuefei (Frontiers in Microbiology, 2021)
Coxsackievirus (CV) A2 has emerged as an important etiological agent in the pathogen spectrum of hand, foot, and mouth disease (HFMD). The symptoms of CVA2 infections are generally mild, but worsen rapidly in some people, posing a serious threat to children’s health. However, compared with enterovirus 71 detected frequently in fatal cases, limited attention has been paid to CVA2 infections because of its benign clinical course. In the present study, we identified three CVA2 strains from HFMD infections and used the cell-adapted CVA2 strain HN202009 to inoculate 5-day-old BALB/c mice intramuscularly. These mice developed remarkably neurological symptoms such as ataxia, hind-limb paralysis, and death. Histopathological determination showed neuronophagia, pulmonary hemorrhage, myofiberlysis and viral myocarditis. Viral replication was detected in multiple organs and tissues, and CVA2 exhibited strong tropism to muscle tissue. The severity of illness was associated with abnormally high levels of inflammatory cytokines, including interleukin (IL)-6, IL-10, tumor necrosis factor α, and monocyte chemotactic protein 1, although the blockade of these proinflammatory cytokines had no obvious protection. We also tested whether an experimental formaldehyde-inactivated CVA2 vaccine could induce protective immune response in adult mice. The CVA2 antisera from the vaccinated mice were effective against CVA2 infection. Moreover, the inactivated CVA2 vaccine could successfully generate immune protection in neonatal mice. Our results indicated that the neonatal mouse model could be a useful tool to study CVA2 infection and to develop CVA2 vaccines.